Quantitative Structural Organization of Bulk Apical Membrane Traffic in Pollen Tubes - Grebnev, Gleb; Cvitkovic, Mislav; Fritz, Carolin; Cai, Giampiero; Smith, Ana-Suncana; Kost, Benedikt (Plant Physiology, 2020)
Pollen tube tip growth depends on balancing secretion of cell wall material with endocytic recycling of excess material incorporated into the plasma membrane (PM). The classical model of tip growth, which predicts bulk secretion, occurs apically, and is compensated by subapical endocytosis, has been challenged in recent years. Many signaling proteins and lipids with important functions in the regulation of membrane traffic underlying tip growth associate with distinct regions of the pollen tube PM, and understanding the mechanisms responsible for the targeting of these regulatory factors to specific PM domains requires quantitative information concerning the sites of bulk secretion and endocytosis. Here, we quantitatively characterized the spatial organization of membrane traffic during tip growth by analyzing steady-state distributions and dynamics of FM4-64-labeled lipids and YFP-tagged transmembrane (TM) proteins in tobacco (Nicotiana tabacum) pollen tubes growing normally or treated with Brefeldin A to block secretion. We established that (1) secretion delivers TM proteins and recycled membrane lipids to the same apical PM domain, and (2) FM4-64-labeled lipids, but not the analyzed TM proteins, undergo endocytic recycling within a clearly defined subapical region. We mathematically modeled the steady-state PM distributions of all analyzed markers to better understand differences between them and to support the experimental data. Finally, we mapped subapical F-actin fringe and trans-Golgi network positioning relative to sites of bulk secretion and endocytosis to further characterize functions of these structures in apical membrane traffic. Our results support and further define the classical model of apical membrane traffic at the tip of elongating pollen tubes.
CRIS-Team Scopus Importer:2020-08-14

Secretion and Endocytosis in Pollen Tubes: Models of Tip Growth in the Spot Light - Grebnev, Gleb; Ntefidou, Maria; Kost, Benedikt (Frontiers in Plant Science, 2017)
Pollen tube tip growth is a widely used model ideally suited to study cellular processes underlying polarized cell expansion. Local secretion supplying material for plasma membrane (PM) and cell wall extension is essential for this process. Cell wall biogenesis requires fusion of secretory vesicles with the PM at an about 10× higher rate than PM extension. Excess material is therefore incorporated into the PM, which needs to be reinternalized through endocytosis. The classical model of tip growth proposes that exocytosis occurs at the apex and that newly incorporated PM material is transported to adjacent lateral regions, where excess material is endocytically recycled. This model was recently challenged based on studies indicating that lateral exocytosis may be balanced by apical endocytosis. This review provides an overview of published data pertaining to exocytosis, endocytosis and vesicular trafficking in pollen tubes. Its key aim is to present classical and alternative models of tip growth in the light of available experimental data. By necessity, the review focusses on pollen tubes of angiosperm models (Nicotiana tabacum, Arabidopsis, Lilium longiflorum), which have been studied far more extensively and grow much faster than structurally strikingly different gymnosperm pollen tubes. Only major transport pathways are considered, which substantially contribute to the mass-flow of membrane material at the pollen tube tip. Growth oscillation, which may be displayed in particular by fast-growing pollen tubes, are not discussed as their influence on the spatial organization of apical membrane traffic is not understood.
Keywords: pollen tube; tip growth; polarized growth; secretion/exocytosis; endocytosis; membrane recycling